Image Compression using Various Methods: A Review (Eurasian Journal of Engineering and Technology, 2022)
A method of image compression eliminates unnecessary and/or irrelevant information and encrypts what remains. It is frequently necessary to discard unrelated and nonredundant data to achieve the required reduction. The subject of how to compress images and which techniques are utilized may emerge. Two types of image compression algorithms, lossless and lossy, are primarily introduced for this purpose: lossless and lossy. Currently, additional strategies are incorporated into the fundamental method. In specific applications, neural network evolutionary algorithms are utilized to compress images. This paper discussed several pictures squeezing approaches. Based on an analysis of different image compression algorithms, a survey of extant research articles is presented in this work. In this study, we examine various available picture compression methods. Compression of images differs significantly from compression of plain binary data. Use different picture compression techniques to resolve these issues.